EDUCAÇÃO INFANTIL: o papel do gestor escolar para a promoção da educação integral da cri - Maria Lília Imbiriba Sousa Colares; Francinara Silva Ferreira; Clênya Ruth Alves Vasconcelos; Adriana Oliveira dos Santos Siqueira (Universidade Federal do Maranhão, 2016)
This text brings a reflection about early childhood education and school manager's role to promote the integral education of the child. It rests on bibliographical analysis, which include the authors Sarmento (2015), Campos (2015), Paro (2015), Palmen (2015), Hora (2010), Valverde (2009) and Pimentel (2007). It appears through the reflections about the themes woven child education, integral education and school management, which first requires a resign in order that children need adequate conditions for their comprehensive development, an issue that has received prominence in brazilian legislation, which seeks to guide actions under educational press against the promotion of integral education. In this scenario, the figure of the child education institution manager emerges as dominant factor to the effectiveness of these actions. Therefore, the manager along with the school staff need to be facilitators of the integral education of the child.